HUBUNGAN PENGETAHUAN DENGAN SIKAP REMAJA PUTRI TENTANG PEMERIKSAAN PAYUDARAH SENDIRI DI SMA NEGERI 7 TANJUNG BALAI TAHUN 2019 - Herlia Sumardha Nasution; Nila Hayati; Ade (Jurnal Ilmiah Kebidanan Imelda, 2020)
Breast cancer is the most feared breast disorder for women, because this disease can not be cured if found at an advanced stage of women is needed to know about breast cancer the purpose of this study is to know there is a Relationship between Knowledge and Attitudes of Young Women About Breast Examination at 7 Tanjung High School Balai Balai 2019 ". This study uses cross-national research design. The population in this study were all students of Tanjung Balai 7th Senior High School in class XI with a sample of 60 students, with the sampling technique of total sampling the number of smapels in this study was 60 people. Data analysis techniques were carried out using univariant and bivariate statistical analysis. The statistical test in this study, used the chi square formula (kai squared) to estimate or evaluate the frequency under investigation has a significant or no relationship, with a 95% confidence level. Based on the results of the study There is a positive and significant relationship between the knowledge and attitudes of young women about breast self-examination in Tanjung Balai 7 High School in 2019, where the p value = 0.032 (p <0.05). For this study can add insight and knowledge for young women to pay more attention to the Dengan gers of breast cancer and prevention by examining their own breasts and can apply to everyday life.